Multiple bone brown tumor secondary to primary hyperparathyroidism: a case report and literature review - Xu, Weibo (Gland Surg, 2019)
Bone brown tumors secondary to primary hyperparathyroidism (PHPT) are rare and only around 2–5% of PHPT patients have multiple bone brown tumor lesions, which are also uncommon in literatures. We found a female patient who got misdiagnosis of multiple malignant bone tumors in our clinical work, she was eventually diagnosed as a brown tumor secondary to hyperparathyroidism. This article records the diagnosis and treatment process, and summarizes similar case reports in the past decade to provide experience in diagnosis and treatment of similar cases that may occur in the future.